2009
DOI: 10.1055/s-0029-1224793
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Impact of Ethnic Cosmetic Surgery: Trends and Potential Financial Impact the African American, Asian American, Latin American, and Middle Eastern Communities Have on Cosmetic Surgery

Abstract: The popularity of cosmetic surgery has increased around the world, and whereas in the past, the patient base consisted of mainly Caucasian individuals, interest in this field has grown among persons of varying ethnic backgrounds. Growing interest enables ethnic populations to contribute to the economic growth of the cosmetic surgery industry and impact the direction of the field in the future. Minority populations accounted for 22% of the cosmetic procedures performed in 2007, with the most common being liposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…In the present study, majority of the patients were female (43 females compared to 17 males), and the mean age in both the groups was <45 years. The younger population, particularly women, is more concerned about the cosmetic outcome of the surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, majority of the patients were female (43 females compared to 17 males), and the mean age in both the groups was <45 years. The younger population, particularly women, is more concerned about the cosmetic outcome of the surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors have contributed to the increased demand for surgical and non-surgical cosmetic procedures among both Caucasians and Asians. These factors include increased cultural acceptance of cosmetic procedures, growing ethnic populations, and media emphasis on personal appearance [ 1 ]. The American Academy of Cosmetic Surgeons’ 2006 Consumer Perception Survey reported that 46% of surveyed consumers would prefer cosmetic surgery to other goods and services including expensive vacations and high-end vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The motivations and desires of patients seeking cosmetic procedures seem to be the same globally, including reducing the appearance of ageing, body contouring and definition, improving and enhancing symmetry, and changing tissue volume [ 1 ]. However, in general, it is believed that the majority of patients who seek cosmetic procedures want to maintain their ethnic identity and do not want to lose important facial features that exhibit racial characteristics [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although cosmetic surgery usually attracts women, some advertisements in Vietnamese magazines and newspapers also include men. The surgery advertisements focus mainly on raising nose bridges and cutting folds into the eyelids (Boras, 2007;Kaw, 1993;Wimalawansa, McKnight, and Bullocks, 2009). The advertised features are ethnically specific, yet the reasons for the increasing percentage of Vietnamese women, as well as a handful of men, choosing such surgery need further exploration.…”
Section: Discussionmentioning
confidence: 99%